Organizations for People - O'Malley, Michael; Baker, William (Tantor Media, Inc., 2020)
For many years, there has been quite a bit of talk about employee engagement as a means to lift corporate profits and reduce absenteeism and turnover. However, this talk has not produced better companies. In fact, the evidence shows that incivility and instances of employee abuse are getting worse. Additionally, with profit as the primary goal of organizations, most employees view any benign treatment they receive as a secondary convenience that will dissipate once corporate fortunes decline. That is, many employees still believe they are expendable in the eyes of their employers. This book turns that equation around by examining the practices of twenty-one companies that put the interests and needs of employees first. The companies featured in this book see it as their mission to offer people a better, more fulfilling life for themselves, and assist with that holistic journey by providing the organizational elements people need to reach their potential. They do this first by creating respectful and kind cultures that treat every person as an equal, sentient partner in the success of the company. Second, they diligently work to satisfy people's basic needs. The result is a web of fellow-feeling: earnest affection among people who feverishly work to live up to both the high standards of the institution and their obligations to one another.
Online resource; Title from title page (viewed February 28, 2020)
Keywords: Personnel management -- Psychological aspects; Quality of work life; Psychology, Industrial; Personnel; Direction; Aspect psychologique; Qualité de la vie au travail; Psychologie du travail; Personnel management; Psychological aspects; Downloadable audio books; Audiobooks; Livres audio